Racism, Prevent and education: insisting on an open space. Issue 4 (9th October 2017) - Haynes, Joanna; Passy, Rowena
Abstract : Purpose: The purpose of this paper is to discuss the links between the Brexit referendum and changes to the nature of racism in Britain, and following on from this, the implications of the counter-terrorist Prevent agenda with regard to universities. Design/methodology/approach: First, the authors discuss the Brexit referendum and its links to changes in the nature of racism in England, drawing on Burnett's (2013) work to demonstrate how "local conditions, national politics and global conditions" have prompted violent racism in new areas of the country. Within this atmosphere of heightened tension, anti-Muslim abuse and attacks have risen over the past two years, with a proportion of these incidents taking place in universities. The authors then examine the implications of the counter-terrorist Prevent agenda, then disturbing trends that characterise students as vulnerable and university life as potentially damaging to wellbeing, and how these link to anti-extremism dialogue that is expressed in an epidemiological and therapeutic language; the vulnerable are framed pathologically, as "at risk" of radicalisation. Findings: The authors argue that educators' statutory duty to "have due regard to the need to prevent people from being drawn into terrorism" is in considerable tension with the university statutory duty to uphold the freedom of speech/academic freedom; this "duty of care" effectively requires university staff to act as agents of the state. The authors argue that this threatens to damage trust between staff and students, restrict critical enquiry and limit discussion, particularly in the current circumstances of sector insecurity that have arisen from a combination of neoliberal policies and falling student numbers. Originality/value: Developing the argument on how these conditions present a threat to the freedom of speech/academic freedom, in the final section, the authors argue that universities must keep spaces open for uncertainty, controversy and disagreement.